The performance pipeline getting the right performance at every level of leadership - Drotter, Stephen J. (Jossey-Bass, 2011)
"The guide that defines the results required at each organizational level to sustain business successIt's not enough to build a company full of people with leadership skills. The Performance Pipeline digs deep into the real work of executing business results at each leadership layer. Filled with lessons and examples from the author's 40 years of experience Shows how to set performance standards, make sure the right work is being done, and remove performance barriers Illustrates how leaders can make the transition to the next level and achieve full performance This book gives leaders in any industry an advantage over the competition"--